Glutamate signalling via a MEKK1 kinase‐dependent pathway induces changes in Arabidopsis root architecture. (6th May 2013) - Forde, Brian G.; Cutler, Sean R.; Zaman, Najia; Krysan, Patrick J.
Summary: A chemical genetic approach has been used to investigate the mechanism by which external glutamate (l –Glu) is able to trigger major changes in root architecture in Arabidopsis thaliana L. An initial screen of 80 agonists and antagonists of mammalian glutamate and GABA receptors, using a specially developed 96‐well microphenotyping system, found none that replicated the response of the root tol –Glu or antagonized it. However, a larger screen using >1500 molecules bioactive in Saccharomyces cerevisiae (yeast) identified two groups that interfered with thel –Glu response. One of the antagonists, 2–(4–chloro‐3‐methylphenyl)‐2‐oxoethyl thiocyanate (CMOT), has been reported to target Ste11, an evolutionarily conserved MAP kinase kinase kinase (MAP3K) in yeast. This led to the discovery that root growth in a triple mekk1 mekk2 mekk3 mutant ( mekk1/2/3 ), defective in a set of three tandemly arranged MAP3Ks, was almost insensitive tol –Glu. However, the sensitivity of mekk1/2/3 roots to inhibition by other amino acids reported to act as agonists of glutamate receptor‐like (GLR) channels in Arabidopsis roots (Asn, Cys, Gly and Ser) was unaffected. Thel –Glu sensitivity of the mekk1/2/3 mutant was restored by transformation with a construct carrying the intact MEKK1 gene. These results demonstrate that MEKK 1 plays a key role in transducing thel –Glu signal that elicits large‐scale changes in root architecture, and provide genetic evidence for the existence in plants of anl –Glu signalling pathway analogous to that found in animals.